Gastric crypt dysplasia: a distinct subtype of gastric dysplasia with characteristic endoscopic features and immunophenotypic and biological anomalies. Issue 6 (9th November 2015) - Kim, Ahrong; Ahn, Sang‐Jeong; Park, Do Youn; Lee, Bong‐Eun; Song, Geum‐Am; Kim, Gwang Ha; Lauwers, Gregory Y
Abstract : Aims: Previous reports have shown that gastric epithelial dysplasia (GED) limited to the crypt (gastric crypt dysplasia, GCD) is commonly identified at the periphery of gastric carcinoma. However, it is unknown whether GCD is endoscopically identifiable, and how it relates to classic GED lesions. Methods and results: We investigated 1196 consecutive endoscopic resections of GED lesions between January 2011 and December 2014. We also evaluated clinicopathological features of these lesions, as well as the immunohistochemical expression of mucin (Muc)2, Muc5AC, Muc6, CD10, Ki67 and p53. We found 51 (4.3%) lesions composed microscopically of GCD among 1196 GED lesions. Those were elevated mucosal lesions (66.7%) similar in colour and texture to the adjacent mucosa (68.6%). GCD was likely to have an antropyloric location and a higher grade than the adenomatous type, similar to the foveolar and hybrid types ( P < 0.05). A gastric immunophenotype was more common in GCD compared to adenomatous GED ( P < 0.05). Ki‐67‐ and p53‐positive cells were more evident in GCD compared to the adjacent gastric mucosa. Conclusions: Our results demonstrated that GCD can be an endoscopically identifiable lesion, sharing many similarities with foveolar and hybrid GED, for which it may represent a precursor lesion in the gastric carcinogenic sequence.